ANALISIS PENGARUH CORPORATE GOVERNANCE STRUCTURE TERHADAP FEE AUDIT EKSTERNAL - Meliani Mukti; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2016)
The aim  of this study  is to examine  the influence  of   corporate  governance   structure  such  as non- executive   board   independence,    non-executive    board   size.   non-executive    hoard   meeting,   audit committee  size,  audit  committee   meeting,   audit  committee   expertise.and   ownership   concentration to the external  audit fee.  17w population   used  in this study  consist  of manufacture  firms   listed  on the Indenesia  Stock  Exchange   in 2012-2014.   The sampling   method  used  in this study  is purposive sampling   and  obtained   33  samples.   This  study  uses  multiple   regression   analysis  for   hypotheses testing.   The   results   of  this  study   show   that   variables   of  non-executive    board   size   and   audit committee   size  had positively   significant   influence   on external  audit fee,  while  variables   of non- executive   board   independence,    non-executive    board   meeting,   audit   committee   meeting,    audit committee   expertise.   and  ownership   concentration   had  no significant   influence   on external  audit fee.